Evolución de las políticas públicas de seguridad ciudadana en Ecuador y su impacto en la filosofía del Buen Vivir. - García Vallejo, José Antonio (Frónesis)
The evolution of public policies on citizen security in Ecuador and their relationship with the realization of Buen Vivir or Sumak Kawsay as a guiding principle of the State were analyzed. The study is justified by the need to understand how the management of security and social welfare directly influences the exercise of human rights and the materialization of an inclusive development model, particularly in the context of increasing violence and social inequality. The research was conducted using a documentary-bibliographic and comparative approach, based on official primary and secondary sources to analyze the governmental periods between 2007 and 2024. The results show that the strengthening of security institutions, investment in social services, and the implementation of comprehensive public policies during Rafael Correa's administration significantly contributed to poverty reduction and the improvement of crime rates. However, since 2017, a sustained decline in public investment has been observed, along with institutional weakening and the fragmentation of security strategies, factors that have led to increased violence and the deterioration of human development indicators. It is concluded that the recovery of citizen security and the consolidation of Buen Vivir in Ecuador require the reorientation of public policies towards an integral human rights approach capable of ensuring conditions of peace and well-being for the entire population.